Designing a platform-based model of civic participation within the smart-city concept for post-war Ukrainian cities - Dunayev, Igor; Gavkalova, Nataliia; Kud, Aleksander (Eastern-European Journal of Enterprise Technologies, 2023)
The object of research is the concept of a smart city. The study considered the problem of interaction between local authorities and citizens in a smart city based on a platform approach. It was determined that the human-centric concept of a smart city involves representing the functions of the city government in the form of specific public services, the purpose of which is to satisfy the needs of citizens. Public participation and active citizenship are recognized as a key component of smart city development. The mechanisms of public participation in the smart city include information, consultations, discussions, public control of finances and joint funds. Multiple digital communication channels, including social networks, instant messengers, websites, e-mail, and various platforms for citizen appeals, could be used simultaneously to communicate through these mechanisms. This leads to a decrease in the effectiveness of interaction. As a result, information related to active public participation on official city websites is fragmented and often out of date. The scalable digital platform serves as a single environment for the exchange of information and resources between citizens and authorities and helps reduce the time and resources spent on organizing such communications. An example of the development of a digital service on the blockchain is given, implemented in the Bitbon decentralized information platform of Ukrainian origin. The practical application consists in ensuring broad citizen participation in filling funds and monitoring their financial transparency. The results of the implementation of platforms for the development of smart cities are organizing open data, encouraging stakeholders to participate in city management, developing innovative creativity and open dialog